2017
DOI: 10.2166/wst.2017.048
|View full text |Cite
|
Sign up to set email alerts
|

Reclaimed municipal wastewater for forage production

Abstract: This study aims to evaluate the possibility of using reclaimed municipal wastewater for agricultural purpose. We assessed the validity of municipal wastewater treatment, analyzing its chemical characteristics before and after the biological stabilization by pond treatment (WSP). The reclaimed municipal treated wastewater (TWW) was used to irrigate Cenchrus ciliaris. Experiments were carried out in greenhouse, from July 2013 to July 2014, comparing the effects of TWW with the water normally used for irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the contrary, Elfanssi et al (2018) found that the mean leaf area of Medicago sativa L. (alfalfa) irrigated with FW decreased, while the mean leaf area of alfalfa irrigated with treated wastewater continued to increase, indicating that irrigation with FW has a positive effect on alfalfa growth. Similarly, Ben Said et al (2017) observed that crops irrigated with FW showed better growth in both growth cycles compared to those irrigated with FW. The quality of irrigation water significantly influenced the height and leaf width of Cenchrus ciliaris (foxtail buffalo grass).…”
Section: Resultsmentioning
confidence: 79%
“…On the contrary, Elfanssi et al (2018) found that the mean leaf area of Medicago sativa L. (alfalfa) irrigated with FW decreased, while the mean leaf area of alfalfa irrigated with treated wastewater continued to increase, indicating that irrigation with FW has a positive effect on alfalfa growth. Similarly, Ben Said et al (2017) observed that crops irrigated with FW showed better growth in both growth cycles compared to those irrigated with FW. The quality of irrigation water significantly influenced the height and leaf width of Cenchrus ciliaris (foxtail buffalo grass).…”
Section: Resultsmentioning
confidence: 79%
“…Additionally, wastewater contains many different types of pathogens that can represent a great risk for human and animal health. However, wastewater, for its richness in biodegradable organic material (carbon and nitrogen) along with macronutrients and micronutrients, may have beneficial effects on soils and crops representing a valid alternative to FW In this study, the municipal wastewater had been treated with the biological stabilization ponds that reduced the biochemical oxygen demand (BOD) and chemical oxygen demand (COD) values and pathogen load (Ben Said et al, 2017), making them more suitable and safer for irrigation purpose. Accumulation of OM in soil through irrigation with wastewater can result in an improvement of soil chemical and physical properties, with consequent positive effects on environment and plants.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the raising demand of sheep and goat meat, it results necessary to find sustainable solution to improve forage cultivation in arid environment, where food, essentially dependent on the rangelands, can affect the economy of countries that otherwise will be forced to import animal proteins, worsening their economic status (Valone et al, 2002). A previous study (Ben Said et al, 2017) evaluated the possibility of reusing municipal TWW to irrigate the tetraploid C. ciliaris , demonstrating that TWW can be a sustainable option to the use of fresh water (FW) for watering this fodder species. In addition, it has been also demonstrated that when irrigated with TWW, ‘tetraploid’ plants improved their growth than plants irrigated with FW (Ben Said et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Safe Reuse. Ines et al (2017) assessed the possibility of using reclaimed municipal wastewater for Water Environment Research, Volume 90, Number 10 -Copyright © 2018 Water Environment Federation agricultural use. It was concluded that the reclaimed municipal wastewater treated with biological stabilization ponds could be used to irrigate fodder due to its low biochemical oxygen demand (BOD), reduced COD, and the absence of pathogens.…”
mentioning
confidence: 99%